The Substantiation of Priority Directions for the Structural and Technological Modernization of the Electricity Generation Sector - Kyzym Mykola O.; Shpilevskyi Volodymyr V.; Miliutin Hlib V. (Problemi Ekonomiki, 2018)
The article substantiates the necessity of the structural and technological modernization of the electricity generation sector of Ukraine in view of the promising directions of technological development of modern energy and the production sufficiency of domestic power engineering. A methodical approach to the selection of priority directions for structural and technological modernization of the Ukrainian electricity generation sector is proposed. The structural shifts in electricity consumption in the country are investigated. The production and consumption of electricity in the country, the specifics of regulation of daily “semi-peak” and “peak” loads, as well as seasonal fluctuations during the year are analyzed. The methods of base-load provision in the united energy system of Ukraine (UES), the level of flexibility of various types of power plants, the distribution of capacities for base-load provision in the UES by types of energy generation are analyzed. Comparison of the main recommended and actual parameters of the energy generation sector based on the data of 2016 is made, and the existence of significant unused reserves of electric power generation is proved. The possibility for optimizing the structure of the energy generation fleet is justified. The main structural measures for eliminating the problems of the national generation of electric power are identified. A comparative structural and technological characteristic of the sphere of electric energy generation is developed. There constructed a matrix of the positioning of technologies for generation of electric power by the adjusted operating expenses and capital investments as well as a matrix of comparison of technologies for generation of electric power by level of their development and level of market development. Comparison of advanced technologies for thermal generation of electric power until 2035 is made. There justified the choice of the list of technologies for electric power generation, which are expedient to introduce at Ukrainian power stations.